PEMENUHAN HAK ATAS BANTUAN HUKUM DALAM PERKARA PIDANA BAGI MASYARAKAT MISKIN KOTA SEMARANG - Pratiwa Eka Chundhamani (Fakultas Hukum Universitas Stikubank, 2019)
The provision of legal aid to the poor is an effort to fulfill and simultaneously implement a rule of law that recognizes and protects and guarantees the human rights of citizens regarding the need for access to justice and equality before the law. The purpose of writing this thesis is to explain the mechanism for providing criminal legal aid for the poor in Semarang City, the fulfillment of the right to criminal legal aid for the poor, and the inhibiting factors for fulfilling the right to criminal legal aid for the poor in Semarang City. The approach method used is juridical normative, descriptive analytical research specifications. The data source used is secondary data. The data collection method used is literature study. This research is presented in the form of a report which is described induction through qualitative data analysis. The results showed that the mechanism of providing criminal legal assistance to the poor in Semarang City was in accordance with the provisions of Law Number 11 of 2016 concerning Legal Aid, Semarang City Regulation Number 1 of 2016 concerning Implementation of Legal Aid and Regulation of the Mayor of Semarang Number 131 of 2016 concerning Guidelines for the Implementation of Semarang City Regional Regulation Number 1 of 2016 concerning the Implementation of Legal Aid. The fulfillment of the right to criminal legal aid for the people of Semarang city so far the fulfillment of the right to legal aid in criminal cases against the urban poor has not been maximized because it has not been felt by all levels of society, especially the poor who do not know about the existence of free legal assistance, besides that it is also constrained by budget constraints. The factors inhibiting the fulfillment of the right to criminal legal aid for the people of Semarang City are funding factors, law enforcement factors and community factors. Keywords : legal aid, criminal cases, poor people